(untitled) - Ajay Puri; Jyoti Kohli; V.J. Chrunjoo (Asian Journal of Medical Research, 2020)
Background: Protein glycation is a spontaneous reaction that is believed to play a key role in the pathogenesis of many clinical disorders. The glycation of proteins is enhanced by elevated blood glucose concentrations. The major form of protein glycation with a clinical consideration is glycatedhaemoglobin (HbA1c). HbA1c is majorly affected by the blood glucose levels alone. Diabetes mellitus is a metabolic disorder characterized by hyperglycemia. Studies have suggested that HbA1c levels in type-2 diabetes mellitus patients mostly remains elevated, yet some such patients, with or without tight glycemic control, have HbA1c levels nearly close to or within the normal reference range.Subjects and Methods:In this study HbA1c, fasting blood glucose levels and post prandial blood glucose levels in normal subjects as well as in patients with Type-2 diabetes mellitus excluding the complicated ones were studied.Results:The present study confirms earlier studies that all these levels are tightly correlated and the corresponding p values were < 0.001 which were significant and was estimated by using student t-test.Conclusion: Thus indicating that glycated hemoglobin (HbA1c) can be used to assess the glycemic status of an individual for attaining the treatment goal of preventing long term complications of diabetes mellitus.